Pitavastatin protects against neomycin-induced ototoxicity through inhibition of endoplasmic reticulum stress - Wu, Yunhao; Meng, Wei; Guan, Ming; Zhao, Xiaolong; Zhang, Chen; Fang, Qiaojun; Zhang, Yuhua; Sun, Zihui; Cai, Mingjing; Huang, Dongdong; Yang, Xuechun; Yu, Yafeng; et al. (Frontiers in Molecular Neuroscience, 2022)
Irreversible injury to inner ear hair cells induced by aminoglycoside antibiotics contributes to the formation of sensorineural hearing loss. Pitavastatin (PTV), a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, has been reported to exert neuroprotective effects. However, its role in aminoglycoside-induced hearing loss remains unknown. The objectives of this study were to investigate the beneficial effects, as well as the mechanism of action of PTV against neomycin-induced ototoxicity. We found that PTV remarkably reduced hair cell loss in mouse cochlear explants and promoted auditory HEI-OC1 cells survival after neomycin stimulation. We also observed that the auditory brainstem response threshold that was increased by neomycin was significantly reduced by pretreatment with PTV in mice. Furthermore, neomycin-induced endoplasmic reticulum stress in hair cells was attenuated by PTV treatment through inhibition of PERK/eIF2α/ATF4 signaling. Additionally, we found that PTV suppressed the RhoA/ROCK/JNK signal pathway, which was activated by neomycin stimulation in HEI-OC1 cells. Collectively, our results showed that PTV might serve as a promising therapeutic agent against aminoglycoside-induced ototoxicity.